A new mechanism for millennial scale positive precipitation anomalies over tropical South America. (1st December 2019) - Campos, Marília C.; Chiessi, Cristiano M.; Prange, Matthias; Mulitza, Stefan; Kuhnert, Henning; Paul, André; Venancio, Igor M.; Albuquerque, Ana Luiza S.; Cruz, Francisco W.; Bahr, André
Abstract: Continental and marine paleoclimate archives from northwestern and northeastern South America recorded positive precipitation anomalies during Heinrich Stadials (HS). These anomalies have been classically attributed to enhanced austral summer (monsoon) precipitation. However, the lack of marine paleoclimate records off eastern South America as well as inconsistencies between southeastern South American continental and marine records hamper a comprehensive understanding of the mechanism responsible for (sub-) tropical South American hydroclimate response to HS. Here we investigate piston core M125-95-3 collected off eastern South America (10.94 ° S) and simulate South American HS conditions with a high-resolution version of an atmosphere-ocean general circulation model. Further, meridional changes in precipitation over (sub-) tropical South America were assessed with a thorough compilation of previously available marine paleorecords. Our ln(Ti/Ca) and ln(Fe/K) data show increases during HS6-Younger Dryas. It is the first core off eastern South America and the southernmost from the Atlantic continental margin of South America that unequivocally records HS-related positive precipitation anomalies. Based on our new data, model results and the compilation of available marine records, we propose a new mechanism for the positive precipitation anomalies over tropical South America during HS. The new mechanism involves austral summer precipitation increases only over eastern South America while the rest of tropical South America experienced precipitation increases during the winter, challenging the widely held assumption of a strengthened monsoon. South American precipitation changes were triggered by dynamic and thermodynamic processes including a stronger moisture supply from the equatorial North Atlantic (tropical South Atlantic) in austral winter (summer). Highlights: South American rainfall anomalies during Heinrich Stadials (HS) depend on latitude. Dynamic and thermodynamic processes responsible for HS precipitation anomalies. Wetter HS eastern South America related to austral summer South Atlantic moisture. Wetter HS Amazonia related to austral winter equatorial Atlantic moisture.